Bibliography of waqf literature produced in India, Pakistan, Bangladesh, Malaysia and Indonesia during the period from (1977-2007) - Rashid, Syed Khalid (Kuwait Aqwaf Public Foundation, 2008)
No bibliography of Waqf literature has ever been compiled in any of the five countries covered by this study. With the help of field-study, 305 material on waqf have been found, covering the period of last thirty years-1977-2007. India having produced 124 waqf materials, during the last thirty years, tops the list, followed by Malaysia (70), Indonesia(43) and Pakistan (28). An analysis of the literature shows that a majority of the literature deal with waqf laws, both classical and modern. Not much attention appears to be paid to contemporary issue like development and management. There is no literature dealing with Shia waqf, a large number which are there in India and Pakistan. Studies on aqwaf happen to be a neglected area of academic studies and research in the universities of the five countries. Malaysia with 2 PhD theses and 21 Master's dissertations in sitting at the top, while Pakistan is at the bottom, with no PhD and Master's dissertations. In recent years, the emphasis is shifting from hypothetical discussions to empirical studies. Governments have also started showing interest in waqf matters with the help of better waqf laws and more popular involvement of the members of both public and the government.